Curating (Post-)Socialist Environments - Schorch, Philipp 1978- HerausgeberIn; Habit, Daniel HerausgeberIn (Ethnografische Perspektiven auf das östliche Europa, 2021)
In which ways are environments (post-)socialist and how do they come about? How is the relationship between the built environment, memory, and debates on identity enacted? What are the spatial, material, visual, and aesthetic dimensions of these (post-)socialist enactments or interventions? And how do such (post-)socialist interventions in environments become (re)curated? By addressing these questions, this volume releases ›curation‹ from its usual museological framing and carries it into urban environments and private life-worlds, from predominantly state-sponsored institutional settings with often normative orientations into spheres of subjectification, social creativity, and material commemorative culture